Hispanic Community-Engaged Research: Community Partners as Our Teachers to Improve Diabetes Self-Management. (September 2019) - Allen, Nancy A.; Colicchio, Vanessa D.; Litchman, Michelle L.; Gibson, Bryan; Villalta, Jeanette; Sanchez-Birkhead, Ana C.
Introduction: Community-based participatory research (CBPR) is a strategy often employed to address public health priorities. We explored how to build effective, trusting relationships with key community stakeholders and a group of Hispanic/Latinos with type 2 diabetes (T2D) to develop culturally appropriate projects. Method: In the process of implementing a Patient-Centered Outcome Research Initiative (PCORI) award, our Community Advisory Board (CAB) met monthly to develop a set of comparative effectiveness research questions along with the interventions to develop specific strategies to improve Hispanic/Latino individuals' self-management of T2D. An agenda was prepared for each meeting targeting the PCORI grant timeline. Notes were taken during these meetings and analyzed to determine effective strategies. Results: Ten strategies were identified that led to the success of this CBPR project and to the current sustainability phase. Instrumental to our success was our partnership with a community health worker (CHW) who co-lead this research project. The CHW and CAB individualized general CBPR strategies to make this project successful in their community. Conclusion: Our community partners became influential knowledge holders throughout this research process. They improved researchers' understanding of how to address the needs of Hispanic/Latino individuals with T2D and how community members could become leaders within their community.